Dampak Interaksi dengan Gadget Terhadap Perkembangan Emosi dan Sosial Anak Sekolah Dasar: Sebuah Tinjauan Literatur - Helmi; Hardiansyah, Rila (Journal of Education and Culture, 2024)
This research explores the impact of gadget use on elementary school children's emotional and social development through a comprehensive literature review. This study covers Scopus-indexed literature from 2019 to 2023, It focuses on how children's usage of gadgets affects their cognitive, linguistic, physical, and social-emotional development. The findings of the study demonstrate that attention span issues can result from excessive gadget use, sleep problems, and decreased physical activity, hindering children's emotional and social development. Children who frequently use gadgets tend to have lower social skills and are less sensitive to the environment around them. Although technology improves language skills and access to educational information, its negative impacts cannot be ignored. Therefore, parents and educators must monitor and limit children's screen time. This study recommends screen time limits based on the child's age: For kids ages 0 to 2, there should be no screen time; for kids ages 3 to 8, there should be less than 60 minutes per day; and for kids ages 6 to 8, there should be no more than 60 minutes per day. Technology use can be maximized without jeopardizing critical areas of a child's development when it is supervised properly.